Insertion of the o-Aminophenol Core into Ninhydrin–Phenol Adducts: Migration of Ninhydrin Carbon Leading to N-Phenylbenzoate-Substituted Phthalimides - Das, Suven; Dutta, Arpita; Maity, Suvendu; Ghosh, Prasanta; Mahali, Kalachand (Synlett, 2018)
An unexpected migration of a ninhydrin carbon bearing a phenolic subunit has been observed when phenolic adducts of ninhydrin reacted with 2-aminophenol in butan-1-ol at the reflux temperature. The products were unambiguously assigned as 2-(1,3-dioxoisoindolin-2-yl)phenyl benzoates on the basis of NMR spectroscopy and X-ray crystallographic analysis.
Keywords: phenols; rearrangement; heterocycles; migration; insertion